The 'industrialisation' of venture capital: new challenges for intermediation issues. (4th April 2006) - Petit, Pascal; Quere, Michel
This paper investigates the comparison between the US and European Venture Capital (VC) industries and their developmental conditions. Some characteristics of the US VC industry cannot be carelessly used as a benchmark for European VC industries. We then distinguish R&D-oriented and market access-oriented VC objectives which leads us to develop a comprehensive approach of the VC industry by insisting on the economic implications of its current industrialisation. The intermediation function, covered by venture capital, is characterised by its sectoral and institutional dimensions. Moreover, accounting for this diversity of VC industries helps in recommending policies that comply with national and local specific requirements.